Seventeen new microsatellites for Tamarix gallica and cross‐amplification in Tamarix species. (22nd January 2020) - Terrones, Alejandro; Juan, Ana
Abstract : Premise: Microsatellite markers were developed for the western Mediterranean tree Tamarix gallica (Tamaricaceae) as part of a study of its genetic diversity and structure. Methods and Results: Seventeen microsatellite markers were developed for T. gallica, 14 of which were polymorphic. These microsatellites have di‐, tri‐, and tetranucleotide repeats with 1–13 alleles per locus and population. Levels of observed and expected heterozygosity ranged from 0.000 to 0.900 and from 0.000 to 0.863, respectively. Six microsatellites showed significant deviations from Hardy–Weinberg equilibrium in at least one population. Cross‐amplification in 19 Tamarix species showed a wide transferability to other species of the genus. Conclusions: The 14 new polymorphic microsatellite markers will be used to assess the genetic diversity and population genetic structure of T. gallica . Additionally, the successful cross‐species amplification suggests their potential usefulness for investigating species delimitation and population genetics in the genus Tamarix .